PROJECTIONS REGARDING THE ALIGNMENT OF THE BRAZILIAN SOCIAL PROTECTION SYSTEM WITH THE REQUIREMENTS OF THE ILO (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
This article analyzes the alignment of the Brazilian Social Protection System with the requirements of the International Labour Organization (ILO), focusing on the challenges of universal coverage and the financial sustainability of Social Security. The general objective is to evaluate the evolution of the social protection system in Brazil, the implications of Constitutional Amendment 103/2019, and the ILO guidelines for an effective and universal system. The study is exploratory qualitative, based on bibliographic and documentary research. The main results indicate that, despite advances in the inclusion and universalization of social security rights, significant challenges remain, especially regarding financial sustainability and the inclusion of vulnerable groups. Amendment 103/2019 represents an important step towards ensuring the long-term viability of Social Security, although its impact on vulnerable workers raises criticism. It concludes that alignment with ILO guidelines requires ongoing structural reforms, inclusive policies, and a holistic approach that considers the needs of society. It is recommended that further studies be conducted to deepen the understanding of the impacts of recent changes and to assess the implementation of best international practices in the Brazilian context.